Is there an informal employment wage premium? Evidence from Tajikistan - Gholam Reza Arabsheibani; Anita V. Staneva (Institute for the Study of Labor (IZA), 2012)
This paper defines informal sector employment and decomposes the difference in earnings distributions between formal and informal sector employees in Tajikistan for 2007. Using the quantile regression decomposition technique proposed by Machado and Mata (2005), we find a significant informal employment wage premium across the whole earnings distribution. This contrast with earlier studies and casts doubt on the recent literature showing that the informal sector is poorly rewarded. It seems to be the case that the informal employment in Tajikistan is the main source of income.
Keywords: C14; J21; J30; 330; formal/informal employment; quantile regression decomposition; Lohnstruktur; Informeller Sektor; Schwarzarbeit; Schätzung; Tadschikistan